Kekuatan Opini Publik di TikTok terhadap Krisis Citra Pertamina pada Isu Pertalite Oplosan - Anida Nadya Abror; Kamelia Malik; Nikmah Hadiati Salisah (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study aims to explain how public opinion on TikTok is formed and develops around the Pertalite adulteration issue, as well as how these perceptions influence Pertamina’s corporate reputation as a national energy company. Using a qualitative approach with netnography and content analysis, the research examines videos, comments, and user interactions during the peak virality of the issue. Data were collected through purposive sampling of TikTok posts with high engagement levels. Analysis was conducted through coding and categorization to identify key patterns in the formation of public opinion. The findings show that public opinion emerges from collective user experiences, reinforcement of negative narratives in comment sections, and repeated sentiments across various unrelated content. This pattern creates a discursive echo that sustains negative perceptions and makes them difficult for the institution to control. Furthermore, Pertamina’s humorous communication strategy was not well received and instead worsened its public image, as it was perceived as inappropriate for a crisis situation. These findings highlight that TikTok’s conversational dynamics play a significant role in shaping reputation crises, requiring companies to develop crisis communication strategies that are more contextual, rapid, and empathetic toward digital interaction cultures.